Ozone: A powerful tool for the fresh produce preservation - Tzortzakis, Nikos G. (My University, 2016)
The consumption of vegetables and fruits has risen noticeably during recent decades, leading to a greater frequency of foodborne illnesses associated with fresh produce. Traditional disinfectants, including chlorinated compounds, fail to adequately control common spoilage microorganisms as well as potential harmful human pathogens. Safe, effective alternatives to halogenated disinfectants are required to reduce spoilage losses, improve food safety, and gain consumer approval. Research and commercial applications have established that ozone (O3) may provide a viable alternative to traditional disinfectants, with some additional benefits documented. This technology has attracted considerable commercial interest, especially because ozone does not leave any residues on the treated produce and it is also accepted by many organic grower organizations. However, several contradictions regarding the efficacy of this technology are often found in the literature and further research is still needed. Different findings could be attributed to a great variability of the research work conditions (ozone generation and application methods, O3 exposure time and concentration, packed produce). Indeed, ozone enrichment induces fruit resistance and suppresses fungal growth-spores production, enhances fruit quality, and may alter gene and protein expression. Each commodity needs to be optimized for the specific ozone application. Consequently, it would be possible to improve its potential as a sanitizer in the food industry.
Keywords: Ozone; Ozonation; Gaseous ozone